2021
DOI: 10.1071/bt21047
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of the therapeutic-honey plants

Abstract: Demand for therapeutic honey is driving establishment of Leptospermum plantations. This study developed micropropagation methods for two species -Leptospermum polygalifolium Salisb. and L. scoparium J.R.Forst. & G. Forst. The study determined how shoot proliferation and adventitious rooting were influenced by the original explant position on the seedling and the concentration of benzyladenine (BA) in the proliferation medium. Hormone-free node culture was highly effective for both species. Nodal explants often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Indeed, the same authors mentioned a significant decrease in bud break rate between the second and third distal nodes probably due to the negative morphogenetic gradient. However, Darby et al [16] found that the original position of the explant in in vitro culture did not influence shoot regeneration in Leptospermum polygalifolium and Leptospermum scoparium. The addition of 0.1mg/L NAA to medium containing 2mg/L BAP was able to stimulate bud break of seeded internodes [17].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the same authors mentioned a significant decrease in bud break rate between the second and third distal nodes probably due to the negative morphogenetic gradient. However, Darby et al [16] found that the original position of the explant in in vitro culture did not influence shoot regeneration in Leptospermum polygalifolium and Leptospermum scoparium. The addition of 0.1mg/L NAA to medium containing 2mg/L BAP was able to stimulate bud break of seeded internodes [17].…”
Section: Discussionmentioning
confidence: 99%
“…In some clones, this dose resulted in extremely high shoot numbers; explants frequently produced extensive callus and multiple short shoots. PGRs play an important role in cytodifferentiation and morphogenesis, regulating the complex processes of cell proliferation, xylogenetic differentiation, and root-shoot differentiation [41].…”
Section: Multiplication Of L Suaveolensmentioning
confidence: 99%
“…In some clones, this dose resulted in extremely high shoot numbers; explants frequently produced extensive callus and multiple short shoots. PGRs play an important role in cytodifferentiation and morphogenesis, regulating the complex processes of cell proliferation, xylogenetic differentiation, and root-shoot differentiation [39].…”
Section: Multiplication Of L Suaveolensmentioning
confidence: 99%